Waqf rules and contemporary applications with special study on the prospects of issuing waqf sukuk in Malaysia / Marwa al-Fares - Marwa , al-Fares (2019)
This study discusses some waqf rules and its contemporary applications with special study on the prospects and possibility of issuing waqf sukuk in Malaysia. Furthermore، this study examines the challenges of issuing waqf sukuk in Malaysia to develop waqf properties and to revive the waqf role in contributing to the welfare of Muslim communities. Malaysia is a well-recognised centre for Islamic finance in general and for sukuk issuance in particular. In 2017، 34 present of total global issuance took place in Malaysia. However، Malaysia does not yet have issued of waqf sukuk. According to Rajaendram (2018), the Perak Ruler said that most of Malaysia's waqaf properties are mosques, madrasahs and cemeteries, and very little waqaf land actually generates income; the current statistics show there are more than 13,500 hectares of waqf land in Malaysia only about 2% has been redeveloped. These lands, if invested and developed efficiently, could generate billions of income for the Malaysian community. Therefore، this study highlights the prospects of using waqf sukuk to develop waqf lands in Malaysia and the challenges facing the issuance of waqf sukuk. This study used the qualitative method، where previous studies were carefully reviewed and supported on interviewer structured. Six interviews were held with Waqf and Sukuk experts in Malaysia to provide a clearer and more comprehensive overview of the issue waqf sukuk. The experts emphasized the importance of using sukuk to develop Waqf properties in Malaysia. They also pointed out that there is still no issuance of waqf sukuk in Malaysia. Experts highlighted the most important points in the Saudi Arabia، Singapore and New Zealand experience in issuing waqf sukuk. They outlined many sharia‘a، legal، regulatory and commercial challenges facing the issuance of waqf sukuk in Malaysia. Then they explained their views on the prospects for the issuance waqf sukuk in Malaysia. Some were very optimistic and believed that Malaysia would issue waqf sukuk very soon، while others felt that there were no prospects for issuing waqf sukuk in Malaysia. After that they expressed their opinions on the importance of issuing a special law (special regulations and guidelines) for the issuance Waqf sukuk like the SRI Sukuk. Some experts felt that there was no need for waqf sukuk guidelines because Malaysia already has general sukuk guidelines. Others considered it necessary and very important to have a special law to issue waqf sukuk in Malaysia.